Neurogenetic fetal akinesia and arthrogryposis: genetics, expanding genotype-phenotypes and functional genomics. Issue 9 (15th October 2020) - Ravenscroft, Gina; Clayton, Joshua S; Faiz, Fathimath; Sivadorai, Padma; Milnes, Di; Cincotta, Rob; Moon, Phillip; Kamien, Ben; Edwards, Matthew; Delatycki, Martin; Lamont, Phillipa J; Chan, Sophelia HS; et al.
Abstract : Background: Fetal akinesia and arthrogryposis are clinically and genetically heterogeneous and have traditionally been refractive to genetic diagnosis. The widespread availability of affordable genome-wide sequencing has facilitated accurate genetic diagnosis and gene discovery in these conditions. Methods: We performed next generation sequencing (NGS) in 190 probands with a diagnosis of arthrogryposis multiplex congenita, distal arthrogryposis, fetal akinesia deformation sequence or multiple pterygium syndrome. This sequencing was a combination of bespoke neurogenetic disease gene panels and whole exome sequencing. Only class 4 and 5 variants were reported, except for two cases where the identified variants of unknown significance (VUS) are most likely to be causative for the observed phenotype. Co-segregation studies and confirmation of variants identified by NGS were performed where possible. Functional genomics was performed as required. Results: Of the 190 probands, 81 received an accurate genetic diagnosis. All except two of these cases harboured class 4 and/or 5 variants based on the American College of Medical Genetics and Genomics guidelines. We identified phenotypic expansions associated with CACNA1S, CHRNB1, GMPPB and STAC3 . We describe a total of 50 novel variants, including a novel missense variant in the recently identified gene for arthrogryposis with brain malformations —SMPD4 . Conclusions: Comprehensive gene panels give a diagnosis for a substantial proportion (42%) of fetal akinesia and arthrogryposis cases, even in an unselected cohort. Recently identified genes account for a relatively large proportion, 32%, of the diagnoses. Diagnostic-research collaboration was critical to the diagnosis and variant interpretation in many cases, facilitated genotype-phenotype expansions and reclassified VUS through functional genomics.